Seed Sovereignty: Analysing the Debate on Hybrid Seeds and GMOs and Bringing About Sustainability in Agricultural Development (Journal of Forest and Livelihood, 2024)
The paper further contributes to the debate on the use of hybrid and Genetically Modified Organisms (GMOs) in Nepal by bringing in the concept of seed sovereignty for sustainable agriculture and food security. Moreover, it argues that this debate needs to be looked at from the food system as a whole and at the corporate sector’s interest to control the whole food system. The way the concept of ‘food sovereignty’ was developed to counter the control of the corporate sector on local agricultural production, the concept of ‘seed sovereignty’ can equally be deployed to save the local genotype, maintain agro-biodiversity and agro-ecology and produce healthy food in an ecologically and climate change-adaptive ways. As the seed is basic to the whole food system, the corporate agricultural sector is precisely hitting at the seed sovereignty of farmers so that they become dependent on them, eventually leading to their monopolistic control over the food system. Therefore, the paper argues that the major concern should be focused on farmers’ seed sovereignty as the first step towards sustainable agriculture.